Beyond the broom cupboard: teaching assistants' reflections upon the wider impact of their specialist dyslexia training. Issue 3 (4th May 2018) - Griffiths, Dominic; Kelly, Kathleen
Abstract: Whilst the government-commissioned Rose Report (2009) on provision and support for dyslexic learners in England called for the deployment of more specialist dyslexia teachers in mainstream schools, the reality seems to be that the job of teaching literacy to children with dyslexia is falling to teaching assistants (TAs). As a result, specialist training courses for TAs have been developed in England. Using the Coldwell and Simkins Training Impact Framework, the present study examines TAs participants' perceptions of the impact of two such local authority-based training programmes, not just in terms of the impact upon their individual practice, but also in terms of their perceptions of the wider impact of their status as a trained 'expert' upon their schools' policies, culture and practice. 'Enabling' and 'blocking' factors influencing this wider impact are identified, and implications for the deployment of specialist TAs and the design of their training courses are discussed.